2021
DOI: 10.1080/21655979.2020.1865607
|View full text |Cite
|
Sign up to set email alerts
|

Clinical relevance of neutrophil-to-lymphocyte ratio and mean platelet volume in pediatric Henoch–Schonlein Purpura: a meta-analysis

Abstract: The association of neutrophil-to-lymphocyte ratio (NLR) and mean platelet volume (MPV) with the severe gastrointestinal (GI) involvement in pediatric Henoch-Schonlein Purpura (HSP) has been reported in many studies. However, the conclusions from the previous studies were controversial. Therefore, for the first time, we performed a meta-analysis to systematically evaluate the relationship of NLR and MPV to the severe GI involvements. We retrieved PubMed, EMBASE, Web of Science, and Chinese National Knowledge In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the study of Kim et al, higher NLR was associated with increased risk of renal impairment or gastrointestinal involvement due to HSP. 17,18 In our dataset, NLR was a weak parameter to predict HSP in general. However, we were only able to evaluate whether patients with HSP showed increased values, we did not investigate whether there was a higher incidence of renal involvement.…”
Section: Discussionmentioning
confidence: 95%
“…In the study of Kim et al, higher NLR was associated with increased risk of renal impairment or gastrointestinal involvement due to HSP. 17,18 In our dataset, NLR was a weak parameter to predict HSP in general. However, we were only able to evaluate whether patients with HSP showed increased values, we did not investigate whether there was a higher incidence of renal involvement.…”
Section: Discussionmentioning
confidence: 95%
“…The extent of therapy is individually adapted on the severity and sites of manifestation. Thus, in an uncomplicated course of immunoglobulin (Ig)A vasculitis, symptomatic supportive treatment and the administration of analgesics for pain relief may be sufficient 21 . Evidence‐based recommendations for the systemic treatment of patients with vasculitis are very limited (Table 8).…”
Section: Vasculitismentioning
confidence: 99%
“…Thus, in an uncomplicated course of immunoglobulin (Ig)A vasculitis, symptomatic supportive treatment and the administration of analgesics for pain relief may be sufficient. 21 Evidence-based recommendations for the systemic treatment of patients with vasculitis are very limited (Table 8). The supportive efficacy of highly potent topical glucocorticoids in vasculitic ulcers is recommended based on empirically supported expert experience.…”
Section: Therapymentioning
confidence: 99%
“…[12][13][14] Some studies have indicated that elevated blood NLR and decreased MPV can be good predictors of HSP in patients with symptoms of gastrointestinal involvement. 15,16 Skin rash and elevated D-dimer levels may also cause GI bleeding. Considering the importance of the immune response in HSP, we hypothesized that immune function abnormalities may cause gastrointestinal bleeding in children with HSP.…”
Section: Introductionmentioning
confidence: 99%